2021
DOI: 10.3390/ijms22052429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tyrosine and Tryptophan in Rats with Diet-Induced Obesity

Abstract: Amino acids tyrosine (Tyr) and tryptophan (Trp) play a significant role in the regulation of energy metabolism, locomotor activity, and eating behavior. We studied the possibility of modulating these processes in obesity by increasing the pool of Tyr and Trp in the experimental diet. As a model of obesity, we used Wistar rats fed a diet with an excess specific energy value (HFCD) for 64 days. Trp led to a normalization of the rats’ body weight almost to the control level, but increased anxiety-like behavior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
2
13
0
2
Order By: Relevance
“…Involvement of the amino acid tryptophan and its metabolites in obesity is supported by other investigators [ 41 ]. Lower serum concentrations of tryptophan and kynurenic acid in obese rats in our experimental model supported previously published human data [ 42 , 43 ], making it imperative to study the numerous metabolites of tryptophan and their role in the development of obesity using a metabolomics analytical platform. More than a 25% increase in the serum concentration of the amino acid tyrosine in the obese group of rats needs to be further studied and interpreted as well [ 44 ].…”
Section: Discussionsupporting
confidence: 83%
“…Involvement of the amino acid tryptophan and its metabolites in obesity is supported by other investigators [ 41 ]. Lower serum concentrations of tryptophan and kynurenic acid in obese rats in our experimental model supported previously published human data [ 42 , 43 ], making it imperative to study the numerous metabolites of tryptophan and their role in the development of obesity using a metabolomics analytical platform. More than a 25% increase in the serum concentration of the amino acid tyrosine in the obese group of rats needs to be further studied and interpreted as well [ 44 ].…”
Section: Discussionsupporting
confidence: 83%
“…In the previous study, tyrosine administration showed a decrease in liver fatty degeneration and a reduction in ALT, and no distinct fatty degeneration was observed in the liver tissue [ 37 ]. In another experiment, fatty degeneration was significantly attenuated in the liver tissue of the tyrosine-treated group, and triglycerides and LDL were normalized in the tyrosine-treated group [ 38 ]. These results appear to be due to the modulation of dopamine metabolism by tyrosine.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, except for Met [ 104 ] and Val [ 105 ], supplementation with other EAAs has been reported to reduce body weight under certain conditions [ 2 , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] ]. However, the results are inconsistent.…”
Section: The Effects Of Essential Amino Acid Supplementation On Body ...mentioning
confidence: 99%